Poly (ADP-Ribose) Polymerase 1 Protein Expression in Normal Pancreas and Pancreatic Adenocarcinoma - Roberto Castiglione; Aldo E. Calogero; Enzo Vicari; Giovanna Calabrini; Anna Cosentino; Placido D’Agati; Filippo Fraggetta; Michele Salemi (Case Reports in Gastrointestinal Medicine)
Pancreatic cancer is a most frequent cancer in Europe, and the majority of cases of cancer of the pancreas are diagnosed above the age of 65. Radical surgery is the first curative treatment of pancreatic cancer, and alternative or combined therapeutic options, in particular, consist of adjuvant or neoadjuvant chemotherapy, with or without radiotherapy. Many factors, including diet and genetics, have been implicated in the development of cancer of the pancreas. Poly (ADP-ribose) polymerase 1 (PARP-1) protein is required for translocation of the apoptosis-inducing factor (AIF) from the mitochondria to the nucleus. It is involved in programmed cell death processes. Different PARP-1 gene expression proteins have been observed in various tumors such as lung, ovarian, endometrial, skin, and glioblastoma. We evaluated the expression of PARP-1 protein in pancreatic adenocarcinoma and normal pancreas tissues by immunohistochemistry. Protein PARP-1 in the nucleus was found in all samples (normal pancreas and pancreatic adenocarcinoma tissues). No cytoplasmic staining was observed in any sample. PARP-1-positive cells resulted higher in the normal pancreas compared with the pancreas with adenocarcinoma. PARP-1 overexpression in prostate cancer tissue compared with normal prostate suggests a greater activity of PARP-1 in these tumors. These findings suggest that PARP-1 expression in prostate cancer is an attempt to trigger apoptosis in this type of tumor, similarl to that reported in other cancers. This finding suggests that PARP-1-mediated cell death pathways are inhibited in this cancer.